Partnerstwo Śródziemnomorskie - Panenka, Alicja (Euro-Mediterranean Partnership, 2008)
Barcelona Process, that was started in 1995, was continued on the meetings of Ministers of Foreign Affairs, which contributed to strengthening the co-operation between countries in order to create the area of respect for human rights and democracy and other common principles as well as political, security, social, cultural and human co-operation. It's not possible to evaluate the realization of the Barcelona Process in unambiguous way, because instead of numbers of success, the Middle East conflict still remains unsolved. The area, in which the biggest success was obtained is the institutionalization of Partnership. Extremely important is the fact of establishment of Euro-Mediterranean Parliament meetings, big success is also bringing into existence of the Anna Lindh Euro-Meditteranean Foundation for the Dialogue Between Countries, that is financed by all the members of Euro-Meditteranean Partnerships and by European Commission. In 2004 European Commission has presented the idea of the strategy of European Neighbourhood Policy. The main objective is to share with New member states the adventages of enlargement that has taken place in 2004.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 10, s. 260-272